Investigating the potential of clinical and biochemical markers to differentiate between functional hypothalamic amenorrhoea and polycystic ovarian syndrome: A retrospective observational study. (9th August 2021) - Abou Sherif, Sara; Newman, Rebecca; Haboosh, Sara; Al‐Sharefi, Ahmed; Papanikolaou, Nikoleta; Dimakopoulou, Anastasia; Webber, Lisa J.; Abbara, Ali; Franks, Stephen; Dhillo, Waljit S.; Jayasena, Channa N.
Abstract: Objectives: Functional hypothalamic amenorrhoea (FHA) is a common cause of amenorrhoea, but diagnosis can be challenging. The aim of this study was to investigate the clinical and biochemical features of FHA, compared to that of polycystic ovarian syndrome (PCOS) and assess the diagnostic performance of the different parameters for differentiating the two conditions. Design and Patients: This was a retrospective observational study. We analysed clinical and biochemical parameters of women diagnosed with FHA and PCOS following specialist assessment at the reproductive endocrine gynaecology clinic, St Mary's Hospital. Results: Compared with PCOS, women with FHA had significantly lower body mass index (BMI; 20.1 ± 2.9 vs. 31.1 ± 7.8 kg/m 2 ; p < .0001) and a thinner endometrium (3.75 ± 2.23 vs. 6.82 ± 3.32 mm; p < .0001). Women with FHA had significantly lower luteinising hormone (LH; 3.46 ± 7.31 vs. 8.79 ± 4.98 IU/L; p < .0001), and lower LH to follicle‐stimulating hormone (FSH) ratio, estradiol, thyroid‐stimulating hormone, free thyroxine and prolactin levels; there was no significant difference in FSH levels. BMI had the greatest predictive performance for FHA (area under the curve [AUC]: 0.93; p < .001), followed by estradiol (AUC: 0.89;  p < .001), LH (AUC: 0.88; p < .001) and LH:FSH ratio (AUC: 0.86; p < .001). Conclusions: Our data provides quantification for diagnostic accuracy of clinical parameters to differentiate FHA from PCOS, namely low BMI, estradiol, LH and LH:FSH ratio. These data could help clinicians more reliably diagnose FHA in women with secondary amenorrhoea.